ANALISIS PENDAPATAN USAHATANI PADI SAWAH DENGAN SISTEM TANAM PINDAH DI DESA BANGKIR KECAMATAN DAMPAL SELATAN KABUPATEN TOLI-TOLI - Tahwil, Tahwil; Lamusa, Arifuddin; Wibawa, I Gede Laksana (Fakultas Pertanian, Universitas Tadulako, 2024)
The objective of this research was to investigate the income level of the paddy rice farmers practicing the transplanting system known as Tapin in Bangkir Village of South Dampal Subdistrict of Toli-Toli District. This research was carried out in Bangkir Village, South Dampal District, Toli-Toli Regency which was selected purposively due to its significant contribution to farm production income in this area. The study was conducted from September to November 2021. The average income the respondent farmers received was IDR 14,352,432. 43/2.12 ha/planting season (PS) calculated from an average production rate of 1,794. 05 kg/2.12 ha/PS and with an average price of IDR 8,000/kg. The total average cost incurred by the farmer was IDR 7,490,082. 21/ha/PS. This resulted in an average net income of IDR 6,862,350/0.23 ha/PS for the paddy rice farmers in Bangkir Village.